In vitro anticancer, antioxidant and DNA-binding study of the bioactive ingredient of clove and its isolation - Suhail, Mohammad (European Journal of Chemistry, 2022)
Cancer cannot be ignored since it is the most dangerous disease because it is a major cause of death globally with 15% mortality. Researchers have been attracted to the plant-based solution of this havoc. Among all plants, Syzygium aromaticum has shown tremendous results in many aspects such as anticancer, antioxidant, and others. All the studies that took place, were done on the plant extract only. No one goes further than this. Hence, an advanced computational chemistry-based method for the characterization and identification of the bioactive ingredients isolated from cloves was developed for the first time. First, different extracts of Syzygium aromaticum plant buds were obtained using different solvents (Water, methanol, chloroform, ethyl acetate, 50% ethanol, and hexane), then each extract was evaluated for its anticancer activity against A549 and H1299 lung cancer cell lines. The fractionation of the most active extract was done using flash chromatography. After that, anticancer evaluation of every fraction was done again. One of the obtained fractions showed the highest anticancer activity. For the identification of the most active fraction the experimental IR and NMR data of it was taken and compared with the computational IR and NMR data of 19 compounds found in cloves. Furthermore, DNA binding affinity and antioxidant activity of the fraction showing the highest anticancer activity were also studied. The presented method of the isolation of the most bioactive ingredient will be the most helpful for all the scientists working in the field of separation science and phytomedicine.